2000
DOI: 10.1021/ja990726z
|View full text |Cite
|
Sign up to set email alerts
|

Primary Reaction of the Titanium-Catalyzed Oligomerization of Phosphorus in the Gas Phase

Abstract: The primary reaction of titanium-catalyzed oligomerization of phosphorus using methylphosphine as a reagent has been studied with a highly accurate quantum mechanical procedure. The reaction proceeds as a two-step process with the titanium atom catalyzing the migration of a hydrogen atom from carbon to phosphorus by delocalizing electrons into its unoccupied d orbitals. Thus in the transition state of the second step it has been clearly identified a two-electron three-center bond among titanium, the phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 27 publications
8
79
1
Order By: Relevance
“…16 O 2 (Linde, 99.9991%), 18 O 2 (Sigma-Aldrich, 99 atom %), Nitrous Oxide (Sigma-Aldrich, 99.0%), and CO 2 (Linde, 99.995%) were introduced into the ultra high vacuum region via a needle valve at constant pressures in the range of 5 × 10 −8 to 5 × 10 −7 mbar. Isotopically enriched targets were used where applicable, 52 Cr (99.9%), 56 Fe (99.7%), 58 Ni (99.9%), 63 Cu (99.3%), 64 Zn (99.4%) (STB Isotope Germany GmbH). Chromium was delivered as a sheet which was used directly.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…16 O 2 (Linde, 99.9991%), 18 O 2 (Sigma-Aldrich, 99 atom %), Nitrous Oxide (Sigma-Aldrich, 99.0%), and CO 2 (Linde, 99.995%) were introduced into the ultra high vacuum region via a needle valve at constant pressures in the range of 5 × 10 −8 to 5 × 10 −7 mbar. Isotopically enriched targets were used where applicable, 52 Cr (99.9%), 56 Fe (99.7%), 58 Ni (99.9%), 63 Cu (99.3%), 64 Zn (99.4%) (STB Isotope Germany GmbH). Chromium was delivered as a sheet which was used directly.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Larger systems were studied by the elimination of weakly bound second-sphere water molecules, providing a probe of progressive solvation . A number of theoretical studies have also explored singly charged cation–water complexes to complement these experiments. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…14,15 In addition, state-specific comparisons have highlighted differences in the chemistry of Cu + ( 1 S) and Cu + ( 3 D). 16,17 Activation of the sigma bond in CH 4 represents the prototypical example of C−H bond activation and is the first step in the conversion of this abundant resource into more useful molecules. Numerous gas-phase studies of methane activation by transition-metal ions have revealed a wealth of mechanistic information regarding this important process.…”
Section: ■ Introductionmentioning
confidence: 99%